1996
DOI: 10.1002/j.1550-8528.1996.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Clinic‐Based Hypocaloric Dietary Intervention Implemented in a School Setting for Obese Children

Abstract: Feasibility of a clinic-based hypocaloric dietary intervention implemented in a school setting for obese children. Obes Res. 1996;4:419-429. The objective of this study was to examine whether a protein-sparing modified fast diet and a hypocaloric balanced diet are effective in a clinic-based dietary intervention implemented in a school setting highrisk weight loss program for superobese (2 140% of their ideal body weight for height [IBW]) children. A group of children from two suburban public schools in New Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 16 publications
(8 reference statements)
3
60
0
Order By: Relevance
“…Weight loss, the most outwardly apparent benefit of the VLCD, is a good example. Our subjects lost an average of 11.4 kg during the diet (5.8 kg/month), which is comparable with that in nondiabetic adolescents (17,22,29) and, in fact, exceeds that of m o s t s t u d i e s i n d i a b e t i c a d u l t s (19,28,30 -32). These results were achieved in a predominantly outpatient setting and without the benefit of a behavioral therapy component.…”
Section: Pharmacologic Treatmentsupporting
confidence: 71%
See 2 more Smart Citations
“…Weight loss, the most outwardly apparent benefit of the VLCD, is a good example. Our subjects lost an average of 11.4 kg during the diet (5.8 kg/month), which is comparable with that in nondiabetic adolescents (17,22,29) and, in fact, exceeds that of m o s t s t u d i e s i n d i a b e t i c a d u l t s (19,28,30 -32). These results were achieved in a predominantly outpatient setting and without the benefit of a behavioral therapy component.…”
Section: Pharmacologic Treatmentsupporting
confidence: 71%
“…RESULTS -The diet was followed for a mean of 60 Ϯ 8 days (range 4 -130 days). All subjects stopped the diet voluntarily, and none experienced nausea, vomiting, dehydration, or other side effects, such as orthostatic dizziness, muscle cramps, fatigue, or halitosis, previously reported in pediatric studies (22).…”
Section: Glycemic Controlmentioning
confidence: 67%
See 1 more Smart Citation
“…25 However, it has been shown that physical training in obese children not only reduced percentage body fat, but also showed positive effects on the sympathetic=parasympathetic balance. 14 Thus, the decrease of blood pressure and heart rate during the weight reduction program, which has also been observed by other investigators, 27,28 suggests a more favorable balance between the sympathetic and parasympathetic system, probably resulting in concomitant reduced production of IL-6.…”
Section: Discussionmentioning
confidence: 60%
“…11,13,14,17,19 One study 10 provided a special school meal program for the overweight children of the study. One study 13 used a protein-sparing modi®ed fast and a hypocaloric balanced diet, in a medically supervised school clinic-based program for superobese children. The programs were conducted either after school or during school hours or a combination of both.…”
Section: Secondary Prevention Effortsmentioning
confidence: 99%